We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
693
1
avatar

The values of $x$ such that $$2x^2 - 6x + 5 = 0$$ are $m+ni$ and $m-ni,$ where $m$ and $n$ are positive. What is $m\cdot n?$

 Feb 11, 2018

Best Answer 

 #1
avatar
-2

Solve for x:

2 x^2 - 6 x + 5 = 0

 

Write the quadratic equation in standard form.

Divide both sides by 2:

x^2 - 3 x + 5/2 = 0

 

Solve the quadratic equation by completing the square.

Subtract 5/2 from both sides:

x^2 - 3 x = -5/2

 

Take one half of the coefficient of x and square it, then add it to both sides.

Add 9/4 to both sides:

x^2 - 3 x + 9/4 = -1/4

 

Factor the left hand side.

Write the left hand side as a square:

(x - 3/2)^2 = -1/4

 

Eliminate the exponent on the left hand side.

Take the square root of both sides:

x - 3/2 = i/2 or x - 3/2 = -i/2

 

Look at the first equation: Solve for x.

Add 3/2 to both sides:

x = 3/2 + i/2 or x - 3/2 = -i/2

 

Look at the second equation: Solve for x.

Add 3/2 to both sides:

x = 3/2 + i/2                  or              x = 3/2 - i/2

So, [ 3/2 + i/2] / [ 3/2 - i/2] =4/5 + (3 i)/5

 Feb 11, 2018
 #1
avatar
-2
Best Answer

Solve for x:

2 x^2 - 6 x + 5 = 0

 

Write the quadratic equation in standard form.

Divide both sides by 2:

x^2 - 3 x + 5/2 = 0

 

Solve the quadratic equation by completing the square.

Subtract 5/2 from both sides:

x^2 - 3 x = -5/2

 

Take one half of the coefficient of x and square it, then add it to both sides.

Add 9/4 to both sides:

x^2 - 3 x + 9/4 = -1/4

 

Factor the left hand side.

Write the left hand side as a square:

(x - 3/2)^2 = -1/4

 

Eliminate the exponent on the left hand side.

Take the square root of both sides:

x - 3/2 = i/2 or x - 3/2 = -i/2

 

Look at the first equation: Solve for x.

Add 3/2 to both sides:

x = 3/2 + i/2 or x - 3/2 = -i/2

 

Look at the second equation: Solve for x.

Add 3/2 to both sides:

x = 3/2 + i/2                  or              x = 3/2 - i/2

So, [ 3/2 + i/2] / [ 3/2 - i/2] =4/5 + (3 i)/5

Guest Feb 11, 2018

24 Online Users

avatar
avatar